Addition of cholesterol alters the hydration at the surface of model lipids: a spectroscopic investigation. Issue 34 (19th August 2022) - Pyne, Sumana; Pyne, Partha; Mitra, Rajib Kumar
Abstract : Cholesterol modifies the flexibility of lipid membranes and allows bulk-like water to protrude into phospholipid interfaces, thus the H-bonds at the interface become weak resulting in faster hydration dynamics. Abstract : Cholesterol is known to modify the phase behavior of model lipid membranes as it makes phospholipid bilayers more structured. Simulation results have shown that the addition of cholesterol allows more bulk-like water to protrude into phospholipid interfaces. However, such claims have not yet been verified experimentally. We have investigated the alteration in the hydrogen bond network structure of water at the surface of two model phospholipids DOPC and DOPG as cholesterol is added into these using ATR-FTIR spectroscopy in the FIR-THz region. Our measurements and analysis led us to probe the collective H-bond network explicitly at the lipid surface. A detailed principal component analysis of the measured data concludes that the water–water H-bond vibration dynamics gets slower at the lipid surface as compared to bulk water, the effect being more prominent in the case of the charged phospholipid, DOPG. However, as cholesterol is added and more bulk-like water protrudes into the liposome interface, the H-bond vibration gets weaker and correspondingly the dynamics gets accelerated.